2013
DOI: 10.3324/haematol.2013.089615
|View full text |Cite
|
Sign up to set email alerts
|

Complement factor H-derived short consensus repeat 18-20 enhanced complement-dependent cytotoxicity of ofatumumab on chronic lymphocytic leukemia cells

Abstract: The antitumor activity of monoclonal antibodies in the treatment of chronic lymphocytic leukemia is mediated mainly by antibody-dependent cellular cytotoxicity and complement-dependent cytotoxicity. Unfortunately, the efficacy of complement-dependent cytotoxicity is strongly restricted due to the expression and acquisition of regulators of complement activation by lymphocytic leukemia cells. Whereas the role of membrane regulators of complement activation, such as CD55 and CD59, has been investigated in detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…26 It was recently shown that the abrogation of fH function by using short-consensus repeat 18-20, representing the C-terminal ligand binding domain, in combination with ofatumumab or rituximab resulted in an increased susceptibility of primary CLL cells to CDC. 91,92 A further synergistic effect was seen upon blockage of fH and CD55/CD59. The decay of C3b to iC3b is strongly mediated by Factor I, for which most of the described CRPs exhibit cofactor function.…”
Section: Inhibition Of Complement Regulatorsmentioning
confidence: 83%
“…26 It was recently shown that the abrogation of fH function by using short-consensus repeat 18-20, representing the C-terminal ligand binding domain, in combination with ofatumumab or rituximab resulted in an increased susceptibility of primary CLL cells to CDC. 91,92 A further synergistic effect was seen upon blockage of fH and CD55/CD59. The decay of C3b to iC3b is strongly mediated by Factor I, for which most of the described CRPs exhibit cofactor function.…”
Section: Inhibition Of Complement Regulatorsmentioning
confidence: 83%
“…The key "zero time" control in step 1 provides additional validation for the paradigm, because the cells in this sample (no deposited C3b) are not lysed when they are reacted in NHS-EDTA. Moreover, prolonged incubation of mAb-opsonized cells in step 1 should lead to Factor I-mediated decay of activated C3b to iC3b and then to C3d [45,46,[51][52][53][54], and the results illustrated in Figure 1A reveal that after a 30 min incubation in step 1, lysis of the cells in step 2 is reduced considerably, thus indicating that a substantial fraction of the deposited C3b fragments must have been degraded to inactive iC3b or C3d.…”
Section: Complement Activation In Two Stepsmentioning
confidence: 89%
“…However, as noted above, prototype in vitro experiments have in fact demonstrated that inhibition of cell-associated complement control proteins CD55 and CD59, as well as inhibition of the action of soluble Factor H can all enhance CDC mediated by both of these mAbs [20,33,53,54,61], thus indicating there is indeed room for improvement. Moreover, levels of CDC higher than 90% are difficult to achieve with RTX or with OFA, even with cell lines, and this is particular evident when a clinically important target, i.e., primary CLL cells are examined [16,63].…”
Section: Modulation Of Effector Functions To Increase Mab-mediated Kimentioning
confidence: 99%
See 1 more Smart Citation
“…C immune mediated tumour cell killing by engaging antibody-dependent-cell-mediated-cytotoxicity, complement-mediated-cytotoxicity and activating cellular phagocytosis (4,17,18). Additionally, immunostimulatory CmAbs can activate T lymphocyte cells through the inhibition of T lymphocyte inhibitory receptors (19).…”
Section: Mechanisms Of Action Of Cmabs: a Targeted Approach With A Prmentioning
confidence: 99%